2018
DOI: 10.1155/2018/8792102
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Eyelid Pressure Using a Blepharo-Tensiometer in Patients with Functional Nasolacrimal Duct Obstruction

Abstract: Purpose To compare the eyelid pressure between patients with functional nasolacrimal duct obstruction (FNLDO) and normal controls using blepharo-tensiometer, and to evaluate the relationship between eyelid pressure and the outcomes of silicone intubation (SI) in patients with FNLDO. Study design Prospective case-control study. Methods We enrolled 36 eyes of 36 patients with suspected FNLDO who underwent SI and 36 healthy eyes of age-matched controls. One eye of each patient with FNLDO was randomly selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The measurement using the blepharo-tensiometer showed that eyelid pressure decreased with age for both the upper and lower eyelids in healthy eyes ( Sakai et al, 2012 ). This pressure increased in dry eye and lid-wiper epitheliopathy ( Yoshioka et al, 2015 ; Yamamoto et al, 2016 ; Yamaguchi and Shiraishi 2018 ) but decreased in functional nasolacrimal duct obstruction ( Kim, Lee, et al, 2018 ). This eyelid pressure is homogenously dissipated and absorbed by the corneal epithelium and conveyed to the underlying tissue.…”
Section: The Impact Of Shear Stressmentioning
confidence: 99%
“…The measurement using the blepharo-tensiometer showed that eyelid pressure decreased with age for both the upper and lower eyelids in healthy eyes ( Sakai et al, 2012 ). This pressure increased in dry eye and lid-wiper epitheliopathy ( Yoshioka et al, 2015 ; Yamamoto et al, 2016 ; Yamaguchi and Shiraishi 2018 ) but decreased in functional nasolacrimal duct obstruction ( Kim, Lee, et al, 2018 ). This eyelid pressure is homogenously dissipated and absorbed by the corneal epithelium and conveyed to the underlying tissue.…”
Section: The Impact Of Shear Stressmentioning
confidence: 99%
“…A previous study that used a tactile pressure sensor showed opposite results, wherein the lower eyelid pressure in patients with functional epiphora was lower than in normal controls [ 20 ]. However, this previous study did not compare lacrimal status between patients with functional epiphora and normal controls [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of laxity is considered normal if the distracted distance is less than 2 mm from the cornea; values higher than 6 mm are considered to indicate laxity. Over time, numerous studies have been conducted to evaluate the use of various devices for the assessment of LET [1,[9][10][11][12][13] . However, most of these instruments, including the clamp and latex sensor, were considered infeasible due to their highly variable displacement distances and the overestimated LET values [1,9] .…”
Section: Introductionmentioning
confidence: 99%